The susceptibility of shi drum juveniles to betanodavirus increases with rearing densities in a process mediated by neuroactive ligand–receptor interaction - García-Beltrán, José María; Johnstone, Carolina; Arizcun, Marta; Cuesta, Alberto; Pérez, Montse; Chaves-Pozo, Elena (Frontiers in Immunology, 2024)
Nervous necrosis virus (NNV) is one of the greatest threats to Mediterranean aquaculture, infecting more than 170 fish species and causing mortalities up to 100% in larvae and juveniles of susceptible species. Intensive aquaculture implies stressed conditions that affect the welfare of fish and their ability to fight against infections. In fact, a higher susceptibility to NNV has been related to poor welfare conditions. In order to analyze the physiological link between stressed conditions and increased susceptibility to NNV, as well as its possible role in the pathogenesis of this disease, we reared shi drum (Umbrina cirrosa) juveniles (30.7 ± 3.10 g body weight), which are expected to be asymptomatic upon NNV infection, at three stocking densities (2, 15, and 30 kg/m3) for 27 days and subsequently challenged them with NNV. We firstly characterized the stressed conditions of the specimens before and after infection and recorded the mortalities, demonstrating that stressed specimens reared at 30 kg/m3 suffered mortalities. However, the viral loads in different tissues were similar in all experimental groups, allowing horizontal and vertical transmission of the virus from asymptomatic specimens. All of these data suggest that shi drum tolerates wide ranges of culture densities, although high densities might be a setback for controlling NNV outbreaks in this species. In an attempt to understand the molecular pathways orchestrating this susceptibility change in stressed conditions, we performed a transcriptomic analysis of four tissues under mock- and NNV-infected conditions. In addition to the modification of the exceptive pathways such as cell adhesion, leukocyte migration, cytokine interaction, cell proliferation and survival, and autophagy, we also observed a heavy alteration of the neuroactive ligand–receptor pathway in three of the four tissues analyzed. Our data also point to some of the receptors of this pathway as potential candidates for future pharmacological treatment to avoid the exacerbated immune response that could trigger fish mortalities upon NNV infection.